Cumulative incidence and associated risk factors of dark, firm and dry (DFD) meat in South African beef carcasses - Webb, E.C. (Edward Cottington) (University of Pretoria, 2022)
Dissertation (MSc Agric (Animal Science))--University of Pretoria, 2021.